Prevalence of Metabolic Syndrome in Hepatitis B Virus Infection: Metabolic Syndrome in Hepatitis B Virus Infection - Munawar, Rana Zohaib; Nazar, Tazeen; Aziz, Bilal; Yousaf, Muhammad Kamran; Mohsin, Nabeel; Nawaz, Kashif (Pakistan Journal of Health Sciences, 2024)
Hepatitis B virus infection is a universal healthcare concern leading to the development of decompensated liver disease, cirrhosis, liver cancer and premature mortality. Likewise, metabolic syndrome caused by unhealthy lifestyle and poor eating habits further increases this risk. Objective: To estimate the prevalence of metabolic syndrome in Hepatitis B virus patients. Methods: This cross-sectional study was executed in the Medical Department of King Edward Medical University, Mayo Hospital, Lahore from 1st August 2022 to 31st July 2023. A total of 200 patients with Hepatitis B virus infection were selected via a non-probability consecutive sampling technique. Waist circumference, blood pressure, serum triglycerides, high-density lipoprotein and blood glucose levels were measured. Patients fulfilling 3 out of 5 criteria were labelled as having metabolic syndrome (MetS). Results: Out of 200 patients of Hepatitis B virus, 153 (76.5%) were male and 47 (23.5%) were female, 136 (68.0%) belonged to the age bracket of 18-40 years and 64 (32.0 %) in the 41-75 years’ age group. The mean age was calculated to be 38.79 ± 5.37 years, the mean BMI was 27.34 ± 5.49 kg/m2 and the duration of Hepatitis B virus infection was 8.84 ± 3.15 months. The prevalence of MetS was observed in 50 (25%) patients of Hepatitis B virus infection. Conclusion: It was concluded that there is a significant proportion of metabolic syndrome among Hepatitis B virus-infected individuals.